Tanke feroelektrične plasti - Lavrenčič, Borut (Vakuumist, 1996)
We are presented the research field of thin ferroelectric layers or films. these films are important part of modern electronic components. We are discussing the relevance of field, selected ferroelectric materials, deposition and characterization techniques. The applications and typical electronic elements have been described in some detail.
Keywords: fizika trdne snovi; tanke plasti